2020
DOI: 10.1016/j.scitotenv.2019.134798
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory analysis of urinary organophosphate ester metabolites and oxidative stress among pregnant women in Puerto Rico

Abstract: Background: Organophosphate esters (OPEs) are used as flame retardants and plasticizers. Oxidative stress, the imbalance of reactive oxygen species and antioxidants, measured prenatally has been associated with adverse birth outcomes including preeclampsia and preterm birth. We are the first study to investigate the relationship between OPEs and oxidative stress among pregnant women.Methods: Pregnant women 18-40 yrs. were recruited in Northern Puerto Rico (n=47) between 2011 and 2015. OPE concentrations of: bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 47 publications
(62 reference statements)
1
16
0
Order By: Relevance
“…Concentrations of BDCIPP and DPHP in our study were comparable to those reported in a recent study of adult National Health and Nutrition Examination Survey (NHANES) 2013-2014 participants [44] while other studies of OPE concentrations during pregnancy had similar concentrations of BDCIPP [19] and DPHP [2,45]. However, concentrations for all other metabolites were generally lower in our study population compared to other studies of pregnant women [1,2,13,57,94]. While we have no explanation for this observation, differences in participant SES, occupation, and residential characteristics may be possibilities.…”
Section: Discussionsupporting
confidence: 83%
“…Concentrations of BDCIPP and DPHP in our study were comparable to those reported in a recent study of adult National Health and Nutrition Examination Survey (NHANES) 2013-2014 participants [44] while other studies of OPE concentrations during pregnancy had similar concentrations of BDCIPP [19] and DPHP [2,45]. However, concentrations for all other metabolites were generally lower in our study population compared to other studies of pregnant women [1,2,13,57,94]. While we have no explanation for this observation, differences in participant SES, occupation, and residential characteristics may be possibilities.…”
Section: Discussionsupporting
confidence: 83%
“…We used linear mixed models (LMM) with a random intercept for subject ID to model each prostanoid measure as the dependent variable, with separate models for each exposure biomarker. The crude models included the metal concentration as the exposure and specific gravity as a covariate to adjust for urinary dilution [ 48 , 59 , 60 ]. The final set of covariates were selected based on a priori knowledge and if their inclusion appreciably changed the effect estimates of metal exposure.…”
Section: Methodsmentioning
confidence: 99%
“…We used linear mixed models (LMM) with a random intercept for subject ID to model each prostanoid measure as the dependent variable, with separate models for each exposure biomarker. The crude models included the metal concentration as the exposure and specific gravity as a covariate to adjust for urinary dilution [43,60,61]. The final set of covariates were selected based on a priori knowledge and if their inclusion appreciably changed the effect estimates of metal exposure.…”
Section: Methodsmentioning
confidence: 99%